Attention and Anxiety - Pacheco-Unguetti, Antonia Pilar; Acosta, Alberto; Callejas, Alicia; Lupiáñez, Juan (Psychological Science, 2010)
Anxiety modulates the functioning of attention. Although the existence of this relationship is clear, its nature is still poorly defined. Added are the facts that different types of anxiety—state or trait—may influence attention differently and that attention is not a unitary system. We studied the influence of such types of anxiety by means of a task that, using emotionally neutral information, assesses the efficiency of three attentional networks: orienting, alerting, and executive control. Results showed a double dissociation. Trait anxiety was related to deficiencies in the executive control network, but state anxiety was associated with an overfunctioning of the alerting and orienting networks.